Parents' Weekend Concert. Photo 148 - Sobecki, Nicki (Tufts Archival Research Center, 2008)
Parents' Weekend Concert. A program saluting the opening of the ÃÃÃ¥ÃLincoln: Forever FreeÃÃÃ¥Ã exhibition in Tisch Library and featuring performances by the Tufts Big Band, Orchestra, Chorale, Chamber Singers, Third Day Gospel Choir and Kiniwe. Aidekman Arts Center, Cohen Auditorium, 8 p.m.